A Developed Version of Conjugate Gradient Method With a New Parameter for Dai-Liao Conjugacy Condition With an Application to Solar Panel - Ahmad Alhawarat; Ramadan Sabra; Mehiddin Al-Baali; Hamid El Hor; Shahrina Ismail; Shahrina Ismail; Ali Jaradat (Science Publications, 2026)
Tier 2- Indexed by SCOPUS/ERA